Proteomic characterization of HaCaT keratinocytes provides new insights into changes associated with SDS exposure - Natalia A. Petushkova (Biomedical Dermatology, 2020)
Abstract Background Using human keratinocyte HaCaT cell line model, we screened for proteins that changed their content due to SDS exposure in non-toxic dose (25 μg/ml, as determined by the MTT assay and microscopic examination) during 48 h. Methods The altered level of proteins from HaCaT keratinocytes exposed to SDS was analyzed by LC-MS/MS approach and quantified using Progenesis LC software. Results The Pathview map of 131 upregulated proteins was built, and enhancement of glycolysis/gluconeogenesis was found. Conclusions The results of our study admit the possibility of promotion of the cutaneous neoplasia and/or the peculiarity of the response of immortalized keratinocytes to the SDS treatment and provide new insights into possible role of SDS as integrator of diverse signaling that influence cell fate decisions.